Serum 25-Hydroxyvitamin D and Adipose Tissue Vitamin D Receptor Gene Expression: Relationship with Obesity and Type 2 Diabetes - Clemente-Postigo, María Mercedes; Muñoz Garach, Araceli; Serrano, Marta; Garrido-Sánchez, Lourdes; Bernal-López, María Rosa; Fernandez-García, Diego; Moreno Santos, Inmaculada; Garriga, Nuria; Castellano-Castillo, Daniel; Camargo, Antonio; Fernández Real, José M; Cardona-Díaz, Fernando; et al. (Endocrine Society, 2015)
Context: The relationship between 25-hydroxyvitamin D [25(OH)D] and obesity and type 2 diabetes is not completely understood. Vitamin D receptor (VDR) expression in adipose tissue (AT) is related to obesity and might be regulated by 1,25-dihydroxyvitamin D3 [1,25(OH)2D3]. Objective: To analyze serum 25(OH)D and VDR gene expression in AT according to body mass index (BMI) and glycemic status and the effect of 1,25(OH)2D3 on AT according to BMI. Design and patients: Two cohorts were studied: 1) 118 subjects classified according to their BMI (lean, overweight, obese, or morbidly obese [MO]) and their glycemic status (normoglycemic [NG] and prediabetic and diabetic [P&D]); and 2) 30 obese subjects (BMI > 30 kg/m(2)) classified as NG and P&D. VDR gene expression was analyzed during preadipocyte differentiation and in vitro stimulation with 1,25(OH)2D3 of AT explants from donors with different BMI values. Setting: University Hospital. Main outcome measures: Serum 25(OH)D, parathyroid hormone (PTH), and AT VDR gene expression. Results: 25(OH)D levels were lower in P&D than NG subjects, significantly so in the lean and MO groups (P < .05). 25(OH)D levels correlated negatively with homeostasis model of assessment for insulin resistance (HOMA-IR) (r = -0.200; P = .032) and glucose (r = -0.295; P = .001), but not with BMI. VDR gene expression was higher in MO than in the other BMI groups (P < .05). 1,25(OH)2D3 increased VDR gene expression in AT from obese patients (P < .05) but not from lean subjects. Conclusions: 25(OH)D levels are diminished in P&D compared to NG subjects, independently of BMI, and are closely related to glucose metabolism variables, suggesting that vitamin D deficiency is associated more with carbohydrate metabolism than with obesity. Moreover, AT has a different response to 1,25(OH)2D3 depending on the degree of obesity.
Keywords: Obesidad; Diabetes; Obesity; Adipose tissue; Vitamin D; Type 2 Diabetes